Ruh dalam Perspektif al-Qur’an dan Sains Moderen - Zaenatul Hakamah (IAIN Kediri, 2015)
The development of interpretation method and its approach have given place for academician to discuss about soul through scientific approach. It raises debate which has not been finished yet. In one side, there is a claim that this approach results inappropriate interpretation of Al-Qur’an. However, in other side, this approach can result contextual meaning of Al-Qur’an. Soul, the mysterious thing in life, can be used to be an object of research in science. Therefore, the research on the interpretation of Al-Qur’an through scientific approach results the definition of soul and the detection of its place which can be explained through scientific research. Keywords: Soul, interpretation of knowledge, scientific perspective